Challenging our understanding of youth sport specialization: an examination and critique of the literature through the lens of Bronfenbrenner`s Person-Process-Context-Time Model - DiSanti, J. S.; Erickson, K. (International Review of Sport and Exercise Psychology, 2021)
The examination of youth sport specialization and athlete participation pathways have been sustained lines of inquiry among multiple branches of the sport sciences. The common consensus in scholarly and practical circles indicates that intensive specialization - particularly at an early age - is a maladaptive pattern of participation that presents risks to an athlete`s physical and psychosocial development. Despite these words of caution, a considerable proportion of athletes continue to engage in specialized participation in contemporary sport settings. To better address this disconnect, this article argues for a reconceptualization of the lens by which sport specialization is studied to better understand the participation pathway process: Specifically, use of Bronfenbrenner`s ecological Person-Process-Context-Time (PPCT) Model. The major tenets and assumptions of this framework are first overviewed in a broad sense, leading into a specific critique and analysis of the sport specialization literature as applied to this model. Finally, three guiding recommendations for encompassing a more ecological, practical approach to examining this phenomenon in future research are offered.